2015
DOI: 10.7439/ijbr.v6i3.1841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Classical music on heart rate variability between genders

Abstract: Background: Listening to music alleviates stress but the gender specific difference in the beneficial response elicited by the music on autonomic function is not clear. Therefore this study has been undertaken to look for the significant difference in the autonomic modulation between males and females on listening to a classical music, Rag Bilahari. Aims& Objectives: To assess the effect of music on autonomic modulation between genders. Materials and methods: 60 medical students between the age of 17 and 20 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As such, a study by Latha et al. ( 2015 ) showed that classical music might give rise to a more evident increase in females' parasympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As such, a study by Latha et al. ( 2015 ) showed that classical music might give rise to a more evident increase in females' parasympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…However, functional MR and PET studies showed that brain regions associated with the control of attention, memory, working memory, emotion, and the limbic system also engage in processing musical auditory information (Salimpoor et al, 2013;Trost et al, 2012). As such, a study by Latha et al (2015) showed that classical music might give rise to a more evident increase in females' parasympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the percent decreases in pulse rate and blood pressure was slightly greater in males when compared to females and this suggest slow music listening has a shift toward vagal activity and is more pronounced in male. 12 In male subjects, the mean pulse rate was increased significantly after listening to fast beat music, whereas the systolic and diastolic blood pressure was increased but not statistically significant. Similarly, in females the pulse rate is increased but not statistically significant, whereas the SBP and DBP were significantly increased.…”
Section: Gender Differences In the Effect Of Musicmentioning
confidence: 95%
“…Some studies have shown HR to decrease by calming music (23), soft slow music (24), and self-selected music (25,26), whereas others suggest no difference (27)(28)(29). Listening to music enhances parasympathetic dominance with a reduction in sympathetic tone (30). Previous studies have shown long-term and short-term beneficial effects of musical auditory stimulation on autonomic function (26,(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%